2006
DOI: 10.1002/mabi.200500185
|View full text |Cite
|
Sign up to set email alerts
|

Boronate‐Containing Copolymers: Polyelectrolyte Properties and Sugar‐Specific Interaction with Agarose Gel

Abstract: Copolymers of N-acryloyl-m-aminophenylboronic acid (NAAPBA) with acryamide (AA), N,N-dimethylacrylamide (DMAA), and N-isopropylacrylamide (NIPAM) were found to adsorb on cross-linked agarose gel (Sepharose CL-6B) in the pH range from 7.5-9.2, due to specific boronate-sugar interactions. The molar percentages of phenylboronic acid (PBA) groups in the boronate-containing copolymers (BCCs), as estimated by 1H NMR spectroscopy, were 13, 10, and 16%, respectively, whereas the apparent ionization constants, the pKa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 28 publications
0
31
0
Order By: Relevance
“…Boronic acid bind reversibly to cis-diols such as carbohydrates, polyvinyl alcohol and glycoproteins (James, 2007;Kuzimenkova et al, 2006). Boronic acids have been utilised in a variety of methods for glucose sensing including fluorescent (Badugu et al, 2004), electrochemical (Yokoyama et al, 1989) and optical detection .…”
Section: Introductionmentioning
confidence: 99%
“…Boronic acid bind reversibly to cis-diols such as carbohydrates, polyvinyl alcohol and glycoproteins (James, 2007;Kuzimenkova et al, 2006). Boronic acids have been utilised in a variety of methods for glucose sensing including fluorescent (Badugu et al, 2004), electrochemical (Yokoyama et al, 1989) and optical detection .…”
Section: Introductionmentioning
confidence: 99%
“…The dependence was also linear from 2 to 20 mM glucose at pH 7.5 (see Figure 3). The increase in sensitivity of the gels to glucose with increasing pH probably resulted from the increased fraction of ionized PBA groups (Kuzimenkova et al, 2006) capable of complex formation with the sugar. The linear calibrations were obtained in 50 mM sodium phosphate buffer at a relatively high ionic strength (ca.…”
Section: Resultsmentioning
confidence: 97%
“…Recently, we have found that random copolymer of acrylamide (Am) and N-acryloyl-m-aminophenylboronic acid (NAAPBA) (13 mol% NAAPBA) undergoes pH-dependent phase transition and forms precipitate in aqueous solutions at pH < 8, due to hydrophobic interactions of neutral PBA-groups (Kuzimenkova et al, 2006). Being copolymerized in water on a glass surface in the absence of any bifunctional cross-linker, the monomers formed semitransparent hydrogels (see Figure 1a) insoluble in water, 50 mM sodium phosphate buffer solutions (pH 6-8) and even in 1 M NaOH.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations